2010
DOI: 10.1111/j.1365-3148.2010.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixed versus variable dose of prothrombin complex concentrate for counteracting vitamin K antagonist therapy

Abstract: This study suggests that a fixed dose of 1040 IU of F IX may be an effective way to rapidly counteract VKA therapy in our patient population and provides a basis for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 12 publications
(15 reference statements)
1
27
0
Order By: Relevance
“…11 In this study, a trend was observed towards a marginally lower proportion of patients who reached the target International Normalized Rate (INR) after treatment with the fixed dose regimen compared to variable doses. Variable dosing is recommended by the manufacturer and is based on patient weight, baseline INR, and target INR.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…11 In this study, a trend was observed towards a marginally lower proportion of patients who reached the target International Normalized Rate (INR) after treatment with the fixed dose regimen compared to variable doses. Variable dosing is recommended by the manufacturer and is based on patient weight, baseline INR, and target INR.…”
Section: Introductionmentioning
confidence: 86%
“…Interestingly, we saw the same trend in difference in mortality rate in our previous pilot study which was performed in one Dutch hospital site when switching from the variable dose regimen to a low fixed dose regime. 11 While bleeding was not a direct cause of death in the majority of patients, it could have a potential prognostic implication as a predictor of poor outcome in clinical assessments. An in depth study has been made of bleeding complications after, for example, bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] In contrast to three-factor PCC products, four-factor PCC products were effective for reducing the INR when used without FFP. The effect of four-factor PCC products on bleeding was similar to that of FFP.…”
Section: Urgent Warfarin Reversalmentioning
confidence: 99%
“…Interestingly, we did see the same trend in higher mortality rate in the variable PCC dose regimen compared to the low fixed dose regimen in our previous pilot study which was performed on one Dutch hospital site. 4 In summary, our cost analyses showed that a cost reduction in PCC with a low fixed dose strategy did not coincide with a cost increase due to utilization of other treatment options for VKA associated bleedings. Furthermore, by treatment of these bleeding emergencies with a low fixed PCC dose strategy, on average 1634 euros per patient to 2100 euros per successfully treated patient was saved com-pared to a variable dosing strategy.…”
Section: Letters To the Editormentioning
confidence: 88%